(untitled) (European Journal of Pure and Applied Mathematics, 2010)
This paper deals with the controllability and observability properties of the mathematical models models (describing systems with thermal memory) consisting of boundary value problems of parabolic type, where the differential equation contains additional integral expressions including ``memory functions" which describe the memory property of the material. The proof of controllability relies on a Carleman type estimate and duality arguments.